Ground-based stratospheric O3 and HNO3 measurements at Thule, Greenland: An intercomparison with Aura MLS observations - Fiorucci, I.; Muscari, G.; Froidevaux, L.; Santee, M. (Atmospheric Measurement Techniques, 2013)
In response to the need for improving our understanding of the evolution and the interannual variability of the winter Arctic stratosphere, in January 2009 a Ground-Based Millimeter-wave Spectrometer (GBMS) was installed at the Network for the Detection of Atmospheric Composition Change (NDACC) site in Thule (76.5° N, 68.8° W), Greenland. In this work, stratospheric GBMS O3 and HNO3 vertical profiles obtained from Thule during the winters 2010 (HNO3 only), 2011 and 2012 are characterized and intercompared with co-located measurements of the Aura Microwave Limb Sounder (MLS) experiment. Using a recently developed algorithm based on Optimal Estimation, we find that the GBMS O3 retrievals show good sensitivity (> 80%) to atmospheric variations between ~ 17 and ~ 50 km, where their 1σ uncertainty is estimated to be the larger of ~ 11% or 0.2 ppmv. Similarly, HNO3 profiles can be considered for scientific use between ~ 17 and ~ 45 km altitude, with a 1σ uncertainty that amounts to the larger of 15% or 0.2 ppbv. Comparisons with Aura MLS version 3.3 observations show that, on average, GBMS O3 mixing ratios are biased negatively with respect to MLS throughout the stratosphere, with differences ranging between ~ 0.3 ppmv (8%) and 0.9 ppmv (18%) in the 17–50 km vertical range. GBMS HNO3 values display instead a positive bias with respect to MLS up to 26 km, reaching a maximum of ~ 1 ppbv (10%) near the mixing ratio profile peak. O3 and HNO3 values from the two datasets prove to be well correlated at all altitudes, although their correlations worsen at the lower end of the altitude ranges considered. Column contents of GBMS and MLS O3 (from 20 km upwards) and HNO3 (from 17 km upwards) correlate very well and indicate that GBMS measurements can provide valuable estimates of column interannual and seasonal variations for these compounds. PNRA 2009/A3.04. Work at the Jet Propulsion Laboratory, California Institute of Technology, was done under contract with NASA Published 2441-2453 2A. Fisica dell'alta atmosfera ...